Redefining Feral Dogs in Biodiversity Conservation - Moreira-Arce, D (Elsevier Ltd, 2022)
Unlike most feral domestic animals, ranging behavior, diet dependence, and human socialization have been used as criteria to define feral dogs. These criteria can obstruct wildlife conservation if decisions depend on identifying ferality in dogs. We argue that diet dependence and human socialization are unnecessary to define ferality in situations where dogs constitute a threat to wildlife. Human-dependent diet and sociability are not exclusive to house dogs; thus, they do not differentiate ferality with certainty, and they have no established testing methods or thresholds. Most notably, they obstruct management by complicating feral dog identification. As a case study, legislation in Chile surrounding dog management does not recognize the existence of feral dogs and bans the application of lethal methods on dogs. This impairs conservation because the current definition makes it impossible to distinguish if a dog is feral at first sight. This is a problem in the small-scale livestock industry, where goat and sheep losses are mainly caused by dogs. Stakeholders could kill attacking dogs to defend their livestock, risking a lawsuit if those dogs were owned, or continue to lose their livelihood. Neither option benefits livestock owners. To not hinder conservation, we propose feral dogs be defined based only on ownership status, ranging behavior, and location in the context of management, and offer a classification based on these criteria. However, we contend that whether a dog is feral is not important for decision-making. Instead, dogs should be controlled if they are found on any public space unaccompanied by humans. © 2021 Elsevier Ltd